STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF ORGANS AND TISSUES OF THE ORAL CAVITY IN WORKERS OF INDUSTRIAL ENTERPRISES OF THE REPUBLIC OF UZBEKISTAN. (Multidisciplinary Journal of Science and Technology, 2026)
The demand for scientific substantiation of the structural and functional state of the tissues and organs of the oral cavity of workers of some industrial enterprises has been determined by analyzing the results of research work, to establish the regularities, direct harmful effects.